2022
DOI: 10.22541/au.165389430.06359791/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Environmental inequality: air pollution and asthma in children

Abstract: Whether you benefit from high-quality urban environments, such as those rich in green and blue spaces, that may offer benefits to allergic and respiratory health depends on where you live and work. Environmental inequality, therefore, results from the unequal distribution of the risks and benefits that stem from interactions with our environment. Within this perspective, this article reviews the evidence for an association between air pollution caused by industrial activities, traffic, disinfection-by-products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Higher VOC concentrations were associated with increased asthma exacerbations [8]. Multiple mechanisms have been proposed, including disruption of the integrity and immunoregulatory function of the bronchial epithelium, induction of allergen sensitization, and promotion of airway reactivity in individuals with preexisting allergens sensitivities [10].…”
Section: Indoor Exposuresmentioning
confidence: 99%
See 3 more Smart Citations
“…Higher VOC concentrations were associated with increased asthma exacerbations [8]. Multiple mechanisms have been proposed, including disruption of the integrity and immunoregulatory function of the bronchial epithelium, induction of allergen sensitization, and promotion of airway reactivity in individuals with preexisting allergens sensitivities [10].…”
Section: Indoor Exposuresmentioning
confidence: 99%
“…Higher air pollutant concentrations are found in urban settings. Multiple longitudinal cohort and epidemiologic studies have demonstrated increased asthma prevalence and symptoms, decreased lung function, and increased airway inflammation in individuals living in areas of lower air quality, cumulating in higher numbers of ED visits [10,21]. Particulate matter (PM) is a mixture of solid and liquid particles that are suspended in the air.…”
Section: Outdoor Exposuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Paciencia et al 12 investigated the association and mechanisms between air pollution and asthma in children along with the precautions that should be taken to reduce the burden of air pollution on asthma. Environmental conditions are not shared equally across the populations, regions, and settings where people live, work, and spend their time.…”
mentioning
confidence: 99%